Rhetoric and the purposes of public education: building discourse for shared responsibility. Issue 4 (4th July 2022) - Knight-Abowitz, Kathleen; Stitzlein, Sarah
ABSTRACT: In this study, we employ discourse analysis of US gubernatorial political advertisements to analyze the discursive struggles over the purposes of public schools. The advertisements are analyzed to demonstrate how rhetoric works to shape consent for dominant, human capital views regarding schooling's purposes, as well as to communicate alternative articulations of schooling's purposes which can disrupt that consent. In the latter exploration, we draw upon the approach of public persuasion, where the public is persuaded to deem something other than dominant economic values as relevant for making education decisions. We analyze alternative contextual cues that can shift citizens' impressions, leading them to weigh conflicting values toward schools differently. We offer narratives that change the meaning citizens make of schools with the aim of building public support for public schools.